INTERNALIZATION OF ISLAMIC VALUES THROUGH RELIGIOUS PRACTICES IN IMPROVING STUDENTS' OBEYANCE OF WORSHIP AT SDN BUMI 1 SURAKARTA: INTERNALIZATION OF ISLAMIC VALUES THROUGH RELIGIOUS PRACTICES IN IMPROVING STUDENTS' OBEYANCE OF WORSHIP AT SDN BUMI 1 SURAKARTA - Widodo; Hariyoto, Hariyoto (Taqrib : Journal of Islamic Studies and Education, 2023)
This research explains the internalization of Islamic values ​​through religious practices in increasing students' devotion to worship at SDN Bumi 1 Surakarta. In this research using field research (field research) with a descriptive approach. The results of the research are the value of devotion, the value of politeness of students towards teachers, tolerance and harmony between school members, both teachers and students, tolerance for fellow school members, discipline in terms of dress and time, concern for fellow school members and community members in need, and Moral values ​​towards the environment, namely the value of cleanliness in terms of preserving the school environment through an internalization process through example and habituation.